Interprofessional Education and Collaborative Practice in Multiprofessional Health Residences in hospital context (Research, Society and Development, 2023)
Objective: to understand how the practices in the Multiprofessional Residency in Health in the hospital context favor Interprofessional Education and Collaborative Practice and how they contribute to the expansion of interprofessional actions. Method: document analysis, carried out through theses and dissertations, with data search in February 2022. Data were analyzed using content analysis, with the aid of the ATLAS.ti 9 Software. Results: 15 documents were included for analysis of content. The analysis resulted in 40 units of meaning, eight units of context and two final categories of discussion. Final Considerations: the Multiprofessional Residency in Health is important to foster interprofessional practices. The perspective of a multi-professional team increases the possibilities for the development of Interprofessional Education and Collaborative Practice, but there are challenges for there to be, in fact, collaboration between professionals.